Evaluation of Implementation of Maintenance Management System for Working Vessels of PT Timur Bahari to Improve Company Financial Performance - Febriansyah, Eki Hikmah; Latief, Yusuf (AIBPM Publisher, 2023)
The working vessel is an important asset for marine contractors, including PT Timur Bahari. It plays important role as main equipment for marine constructions, crew accommodation, and marketing tools for the company. Recognizing the pivotal role of working vessel, any downtime would result in unproductive and reducing company’s revenue. On the other hand, uptime is expected to always be at the high level so that working vessels becomes vital to the company’s Financial Performance. The study utilizes survey methods, literature reviews, and case study. The conclusion of this study demonstrates that integrating the Maintenance Management System with the Business Process can significantly enhance the company’s Financial Performance.